1985
DOI: 10.1099/00222615-20-3-325
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Properties Of Staphylococcus Aureus Strains of the New Epidemic Phage Type-95

Abstract: SUMMARY. Three hundred and seventy-one penicillin-resistant Staphylococcus aureus strains of phage type 95 isolated in the years [1977][1978][1979][1980][1981][1982][1983] were investigated. They had characteristic resistance patterns to cadmium (Cd), arsenate (As) and mercury (Hg). Most were susceptible to all three heavy metals; 25 strains were resistant to As only and one to Cd and As. The susceptible strains had a uniform medium level of penicillinase production, whereas the As-resistant strains produced l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1986
1986
1995
1995

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The difficulties in using the chromogenic cephalosporintest suggests that the p-lactamase produced by strains of phage type 95 may have low affinity for cephalosporins. Furthermore, the strains of type 95 have in a previous study (16) been found to lose its P-lactamase plasmid very easily by storage of the strain. False negative results when testing for p-lactamase production is therefore a risk if the strain is not totally freshly cultured.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The difficulties in using the chromogenic cephalosporintest suggests that the p-lactamase produced by strains of phage type 95 may have low affinity for cephalosporins. Furthermore, the strains of type 95 have in a previous study (16) been found to lose its P-lactamase plasmid very easily by storage of the strain. False negative results when testing for p-lactamase production is therefore a risk if the strain is not totally freshly cultured.…”
Section: Discussionmentioning
confidence: 95%
“…This problem has already been observed in our laboratory. The problems with strains of the phage type 95 are of some concern since these strains are increasing in number these years ( 16).…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations on S. aureus strains of type 95 including only betalactamase production and heavy metal resistance pointed to the possibility that all the As-resistant strains belonged to one single clone, and that the remaining few strains with As-resistance and high beta-lactamase production might either be a totally separate, not so widespread, clone or might be a variant of the original clone with a change in the beta-lactamase plasmid including introduction of Asresistance [7]. In the present investigations three newer typing methods: multilocus enzyme electrophoresis, pulsed-field gel electrophoresis and lectintyping have been selected to represent three fundamentally different typing principles: phenotypically expressed differences in the produced isoenzymes and surface-components as well as differences in the gene-sequences.…”
Section: Discussionmentioning
confidence: 99%
“…During [7], and comprised 10 strains with high beta-lactamase production and As-resistance (strain nos 1, 5, 7, 9, 10 and 31-35) and 10 susceptible strains with medium production. In addition, 15 [1].…”
Section: Bacterial Strainsmentioning
confidence: 99%
See 1 more Smart Citation